2016
DOI: 10.1159/000447846
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Modulates Apoptosis in NRK-52E Cells and Activates Fas/FasL Through the MLK3-MKK7-JNK3 Signaling Pathway

Abstract: Background/Aims: The hepatitis B virus X protein (HBx) contributes to HBV-induced injury of renal tubular cells and induces apoptosis via Fas/FasL up-regulation. However, the mechanism of Fas/FasL activation is unknown. Recent studies indicated that HBx induction of apoptosis in hepatic cells depends on activating the MLK3-MKK7-JNKs signaling module, which then up-regulates FasL expression. In this study, we used NRK-52E cells transfected an HBx expression vector to examine the role of the MLK3-MKK7-JNKs signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…HBx is a promiscuous trans-activator that modulates both viral and cellular promoters through a direct interaction with nuclear transcription factors or via cytoplasmic signal transduction [5]. The protein is shown to affect several cellular processes including reduction of adhesion of podocytes [6], modulation of apoptosis in kidney cell [7] and downregulation of microRNA-145 in HCC [8]. HBx affects cell cycle progression by inducing different signaling pathways, deregulating cell cycle checkpoints, and by protein degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBx is a promiscuous trans-activator that modulates both viral and cellular promoters through a direct interaction with nuclear transcription factors or via cytoplasmic signal transduction [5]. The protein is shown to affect several cellular processes including reduction of adhesion of podocytes [6], modulation of apoptosis in kidney cell [7] and downregulation of microRNA-145 in HCC [8]. HBx affects cell cycle progression by inducing different signaling pathways, deregulating cell cycle checkpoints, and by protein degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported suppression of apoptosis by HBx through activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), cAMP response element-binding protein (CREB) and phosphatidylinositol 3-kinase (PI3K) pathways, and survivin protein [13][14][15]. Other studies have shown that HBx induces apoptosis by activation of caspases and c-Jun amino-terminal kinase (JNK) pathway [11,16].…”
Section: Introductionmentioning
confidence: 99%
“…HBx, a regulatory protein, can stimulate multiple host pathways including p38, ERK, JNK and NF-κB [20, 42, 43]. Large surface protein activated p38 and NF-κB [44, 45], while C-terminally truncated middle surface protein activated ERK2 [46], NF-κB and other pathways [47].…”
Section: Discussionmentioning
confidence: 99%
“…Another death receptor, Fas, and its ligand FasL are upregulated in rat renal tubular epithelial cells (NRK-52E) transfected with HBX, and this increase is due to the activation of the MLK3-MKK7-JNK pathway [ 156 ]. The Fas sensitivity is reconstituted in HBX transgenic mice through the decrease of BCL-2, despite no direct interaction between HBX and BCL-2 family members [ 70 ].…”
Section: Hepatitis B Virus and Apoptosismentioning
confidence: 99%